Antibiotic knowledge and influencing factors among residents in China: a cross-sectional survey - Sixian DU; Yaqing LIU; Xiaoxu YIN; Haoran NIU; Feng JIANG; Liwen GONG (Zhongguo gonggong weisheng)
ObjectiveTo understand the level of antibiotic knowledge among residents with different demographic characteristics, identify influencing factors, and explore the association between antibiotic knowledge and inappropriate medication behaviors. This study aims to provide reference data for national policymakers to develop more precise antibiotic usage regulations. MethodsFrom July to September 2023, we distributed 932 questionnaires to residents in 44 cities (counties) across 21 provinces (municipalities) in China. The collected data included demographic characteristics and mastery of antibiotic-related knowledge across nine dimensions (such as treatment course and usage cycle). Fourteen antibiotic-related knowledge questions were scored, with 1 point per question. Respondents were divided into high and low scoring groups based on their average scores. Stepwise linear regression and multivariate logistic regression were used to explore factors causing differences in antibiotic knowledge among respondents with different characteristics. The Spearman correlation coefficient was used to examine the correlation between public antibiotic knowledge and self-medication behaviors. ResultsThe study included 879 valid respondents, with a 62.34% overall awareness rate of antibiotic-related knowledge. Among them, 84.07% (739 people) mistakenly identified antibiotics as anti-inflammatory drugs; the average score for antibiotic knowledge was 8.73 ± 3.212 points. According to the multivariate logistic regression analysis, antibiotic knowledge scores were significantly influenced by the following factors (all P < 0.05): individuals with middle school education or below compared to those with a master′s degree or above (β = – 2.047, OR = 0.129), those with a medical education background compared to those without (β = – 1.430, OR = 0.239), full-time workers compared to other occupations (β = 0.387, OR = 1.472), healthcare workers compared to non-healthcare workers (β = – 0.674, OR = 0.510), individuals with chronic diseases compared to those without (β = 0.753, OR = 2.123), and those who self-rated their health as "very good" compared to "average" (β = 0.647, OR = 1.910). The Spearman correlation test revealed a positive correlation between antibiotic knowledge scores and self-medication behaviors with antibiotics (\begin{document}$ ρ_{s} = 0.399 $\end{document}, P < 0.05). ConclusionsThe level of antibiotic knowledge among residents in China is limited. The government should tailor health education to different population groups to enhance residents′ understanding of the efficacy, classification, applicable symptoms, and risks of antibiotic resistance. This approach could help reduce the frequency of inappropriate antibiotic use among the Chinese population.